AI-based multi-PRS models outperform classical single-PRS models - Klau, Jan Henric; Maj, Carlo; Klinkhammer, Hannah; Krawitz, Peter M.; Mayr, Andreas; Hillmer, Axel M.; Schumacher, Johannes; Heider, Dominik (Frontiers in Genetics, 2023)
A polygenic risk score (PRS) calculates the risk for a specific disease based on the weighted sum of associated alleles from different genetic loci in the germline estimated by regression models. Recent advances in genetics made it possible to create polygenic predictors of complex human traits, including risks for many important complex diseases, such as cancer, diabetes, or cardiovascular diseases, typically influenced by many genetic variants, each of which has a negligible effect on overall risk. In the current study, we analyzed whether adding additional PRS from other diseases to the prediction models and replacing the regressions with machine learning models can improve overall predictive performance. It turned out that multi-PRS models outperform single-PRS models significantly on different diseases. Moreover, replacing regression models with machine learning models, i.e., deep learning, can also improve overall accuracy.